Early Tuvan Layer in Buryat Ethnic Composition: Quu, On, Onqot, Irkit, Qol - Nanzatov, Bair Z. (The New Research of Tuva, 2021)
The article supplements and expands the author’s experience of research into the origin of Buryat ethnonyms Qooγoy, Onγoy, Onqotoi, Irkidei, Qoltubai, which have been reliably known since the 17th century according to Russian sources. The interest in this group of ethnonyms is justified by their relationship with the ethnonyms Quular, Ondar, Irgit, Qol, known among Tuvans, as well as with the presumably early Tuvan ethnonym Onqot, which also have parallels among the Altaian, Khakass, Yakuts, Kirghiz, Kazakhs, Altai Uryankhai, Darkhats, Khalkha, Khamnigan, Urats, etc. The research methodology is based on the word-formation and semantic analysis of ethnonyms, comparative historical, linguo-geographical and etymological methods. The presence of these ethnonyms in the Buryat environment once again reflects the versatility of the Turkic and Mongolian relations. Their belonging to a single group of tribes, whose genealogical ancestor was Oboγon (his image in Yakut legends is known as Omoγoi / Omoγon), allows us to trace the Tuvan, Buryat and Yakut ethnic ties. The presence of the ethnonym Qoltubai in the ethnic composition of Buryats that was recorded in the 17th century makes it possible to determine that it had existed at least a century before the penetration of Russians into Buryatia. The recorded endings of the genitive case –oi, with variants –dei and –toi, as well as the presence of the plural ending –s in the Yakut form of Ergis allow us to place the date as far back as the time of the Middle Mongolian language. The presence of such ethnonyms as Quular, Ondar, Irgit, and Qol in the Tuvan environment shows the parallel development of these variants. As a result of the study, an early Tuvan (Toba) layer was identified in the ethnic composition of Buryats; the identified areas of distribution of ethnonyms have made it possible to outline the East Sayan and Prikhubsugul region as the zone of their initial diffusion.